(untitled) (Bangladesh Journal of Medical Education, 2019)
Objective: To examine the ways and means of practice of formative assessments in undergraduate medical education of Bangladesh. Methods: This descriptive study was conducted in at four conveniently selected medical colleges of Dhaka, Bangladesh. Views of 174 teachers and 332 students were collected using four self-administered semi-structured questionnaires. Results: It was found that majorities of the teachers followed the MBBS curriculum (93%), academic calendar (60%), order of head of the department (57%), text book (64%), experience from past examinations (55%), and their own classes (43%) during assessing the students in the formative examinations. On the other hand, the students followed classes of teachers (98%), textbooks (93%), guide books (73%), questions of their past examinations (68%), advice of senior students (61%) and opinions of classmates (59%) to prepare themselves for their formative assessments. The students mentioned that they required very high or high level of recall knowledge (87%), clear understanding (90%) and application of their learning in new situation (73%) during appearing the formative assessment. The students also mentioned that the uses of ’documented questions’ by typing the questions on question-paper / question-card were given only 31% cases in the card final and 56% in term final structured oral examinations (SOE) boards. Sometimes, there were ’no written documented question’ in the SOE and the examiners asked the questions of their own choice in the card final ((40%) and term final (12%) examinations. Sometimes, only the ’contents were written’ in the question cards and the examiners asked the viva based on the content lists in the card final (45%) and term final (48%) examinations. Some students also mentioned that the examiners provide clues if someone fails to answer the questions in item (38%), card final (26%) and term final (32%) examinations. Conclusion and recommendation: The study recommended that the teachers of the medical colleges should be trained up for proper practice of all areas of the assessments as per the standards and curriculum. Bangladesh Journal of Medical Education Vol.10(1) 2019: 2-5